Confronting Information Asymmetries: Evidence from Real Estate Markets - Garmaise, Mark J.; Moskowitz, Tobias J. (Review of Financial Studies, 2004)
There are relatively few direct tests of the economic effects of asymmetric information because of the difficulty in identifying exogenous information measures. We propose a novel exogenous measure of information based on the quality of property tax assessments in different regions and apply this to the U.S. commercial real estate market. We find strong evidence that information considerations are significant. Market participants resolve information asymmetries by purchasing nearby properties, trading properties with long income histories, and avoiding transactions with informed professional brokers. The evidence that the choice of financing is used to address information concerns is mixed and weak.